2022
DOI: 10.1002/glia.24156
|View full text |Cite
|
Sign up to set email alerts
|

LRRC8Ais dispensable for a variety of microglial functions and response to acute stroke

Abstract: Microglia, resident brain immune cells, are critical in orchestrating responses to central nervous system (CNS) injury. Many microglial functions, such as phagocytosis, motility and chemotaxis, are suggested to rely on chloride channels, including the volume‐regulated anion channel (VRAC), but studies to date have relied on the use of pharmacological tools with limited specificity. VRAC has also been proposed as a drug target for acute CNS injury, and its role in microglial function is of considerable interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…A recent study utilized M/Mφ-specific LRRC8A knockout mice and pharmacological inhibition of LRRC8A and demonstrated LRRC8A channel was necessary for cell volume regulation but not involved in the phagocytic activity, cell migration, or p2yr12 dependent chemotaxis of microglia. 21 This is consistent with our result that lack of LRRC8A did not affect the cell phagocytosis mediated by the AMPK-Nrf2-CD36 axis in BV2, microglia, and RAW264.7 cells. However, the inhibitory effect of LRRC8A enhanced the phagocytosis of cells cotreated with hemin.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A recent study utilized M/Mφ-specific LRRC8A knockout mice and pharmacological inhibition of LRRC8A and demonstrated LRRC8A channel was necessary for cell volume regulation but not involved in the phagocytic activity, cell migration, or p2yr12 dependent chemotaxis of microglia. 21 This is consistent with our result that lack of LRRC8A did not affect the cell phagocytosis mediated by the AMPK-Nrf2-CD36 axis in BV2, microglia, and RAW264.7 cells. However, the inhibitory effect of LRRC8A enhanced the phagocytosis of cells cotreated with hemin.…”
Section: Discussionsupporting
confidence: 93%
“… 19 , 20 Whereas loss of the microglial LRRC8A channel did not affect microglial morphology nor the extent of brain damage. 21 In the peripheral system, the macrophagic LRRC8A channel participates in the hypotonicity-induced NLRP3 inflammasome activation and the process of pyroptotic cell swelling. 22 However, our knowledge of the expression and function of the LRRC8A channel in ICH, which is a more lethal stroke subtype where M/Mφ plays a vital role in its progression by accelerating hematoma clearance and modulating inflammation, is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Then we used a non-selective VAAC inhibitor, 5-nitro-2-(3phenylpropylamino) benzonic acid (NPPB) 58 , to address whether the VAAC contributes to the microglia-node interaction after injury. Similar to PSB, VAAC blocker affects microglial ramification and impairs its laser response 60,61 . Injection of 10 ul 1.5mg/ml NPPB significantly abolished laser injury-evoked chemotaxis of microglial processes within 1.5-hour post injection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Future investigations using gene expression profiling and live-cell imaging will shed more light on the detailed mechanisms underlying Swell1 channel-mediated microglia activation. Notably, using a similar cKO mouse model, a very recent study reported that loss of Swell1 did not affect morphological changes of brain microglia upon ischemic stroke injury ( 43 ). In addition, Swell1 appears to be dispensable for microglia migration and chemotaxis following focal laser injury in the brain ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, using a similar cKO mouse model, a very recent study reported that loss of Swell1 did not affect morphological changes of brain microglia upon ischemic stroke injury ( 43 ). In addition, Swell1 appears to be dispensable for microglia migration and chemotaxis following focal laser injury in the brain ( 43 ). Thus, the regulation of microglial activation by Swell1 may be dependent on the injury type, location, and specific pathophysiological context.…”
Section: Discussionmentioning
confidence: 99%